Anesthetic Implications of the New Guidelines for Button Battery Ingestion in Children. (March 2020) - Hoagland, Monica A.; Ing, Richard J.; Jatana, Kris R.; Jacobs, Ian N.; Chatterjee, Debnath
Abstract : Button battery ingestions result in significant morbidity and mortality in children—before, during, and even after removal. The injuries created by a button battery lodged in the esophagus develop rapidly and can be severe. The current of the button battery, conducted through saliva and the tissue drives a highly alkaline caustic injury, leading to liquefactive tissue necrosis. In June 2018, new guidelines were released from the National Capital Poison Center, which include the use of preoperative protective, pH-neutralizing and viscous barrier interventions with honey and/or sucralfate administered within 12 h of ingestion. In addition, the use of postremoval irrigation of the esophagus with 50–150 mL 0.25% acetic acid is done in the operating room to help neutralize the site of tissue injury. Given that anesthesiologists play an important role in the management of esophageal foreign body removal, the entire specialty needs to be aware of the supporting data behind this and general perioperative considerations for management and potential complications of button battery ingestion.